The poetic dialogue in the poetry of Sliman Djouadi - zair, ibrahim; lebachi, abdelkader (The Notebooks of the Algerian Poetics Laboratory Journal, 2025)
This research sheds light on the use of dialogue in contemporary Algerian poetry, focusing on the works of sliman djouadi. It examines dialogue not as a narrative technique studied through narrative tools and methodologies, but rather in terms of its contribution to the poetic essence of the poem. The study explores both types of dialogue of djouadis poetry. Internal and external , additionally, it uncovers another form at dialogue in this poem- the dialogue with literary texts. The aim is to reveal how this narrative technique is adapted to serve the poetic nature of the poem in a manner distinct from conventional narrative approaches. This adaptation aligns with the unique qualities of poetry by manipulating the elements of dialogue and shifting the interaction from the characters to the audience